DETECTION OF FRAUDULENT FINANCIAL STATEMENT USING HEXAGON FRAUD THEORY A LITERATURE REVIEW - Ridwan, Yolanda Arvilia (JURNAL AKUNTANSI DAN AUDITING, 2023)
This research aims to provide information about how the detection of financial statement fraud that can occur in Indonesia is related to the hexagon theory of fraud. This research uses a systematic literature review methodology in detecting fraudulent financial statements. Found 20 articles between 2011-2021 on google scholar. purposive sampling is used in this article. The results of this literature research can help future researchers to develop more in-depth fraud research in the future. Some of the variables that appear in the selected articles can be a reference for subsequent researchers regarding fraudulent financial statements, such as expanding the object, expanding the scope of the investigation, and adding research factors.